Analyzing The Moderating Role Of Government Support In The Intention To Adopt Halal Practice: Evidence From MSMEs In Indonesia - Fitri, Raisa (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2025)
The purpose of the study is to determine the moderating role of government support on the intention to adopt halal, which is influenced by the following factors: religiosity, consumer demand, and expected revenue in MSMEs.This research used a quantitative approach with hypothesis testing. Data distribution using an online questionnaire by researchers directly and in stages with the assistance of surveyors from the cooperative office; the number of data that met the criteria was 194 MSME respondents in Malang City. To determine the influence of the moderating role of government support on the intention to adopt halal practices, this study used SEM-PLS analysis. This study found that government support does not moderate the intention in adopting halal practices, which is influenced by the following factors: consumer demand, and expected revenue. The findings of the direct influence that religiosity, consumer demand, expected revenue and government support affect the demand for adoption of halal practices.